Impact of Psychological Conditions and Physical Environment on Hospitality Services through Patient Experience - Eva Khodijah; Mohamad Reza Hilmy; Nofierni Nofierni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Modern healthcare services are undergoing transformation toward a more humanistic and patient-centered approach, emphasizing hospitality based services in hospitals. However, many healthcare institutions, particularly in outpatient settings, have not fully adopted this concept. Patients often experience psychological distress, and when coupled with an unsupportive physical environment, their comfort and overall experience may be diminished. These conditions can negatively affect perceptions of service quality, patient satisfaction, and loyalty toward hospital services. This study aimed to analyze the influence of patients’ psychological conditions and the physical environment on hospitality-based services, with patient experience as an intervening variable, at the internal medicine outpatient clinic of BM Hospital. A quantitative research design using a cross-sectional approach was employed. The study involved 200 respondents selected through purposive sampling. Data were collected using structured questionnaires with Likert-scale items and analyzed with Structural Equation Modeling Partial Least Squares (SEM-PLS). The results showed that patients’ psychological conditions, the physical environment, and patient experience simultaneously and significantly influenced hospitality-based services. Hypothesis testing confirmed that both psychological conditions and the physical environment had a direct and significant impact on hospitality-based services. Furthermore, patient experience played a mediating role, strengthening the relationship between these factors and perceived service quality. The findings highlight the need for hospitals to integrate psychological support and a conducive physical environment into outpatient care delivery. Enhancing these dimensions can improve patient experience, foster greater satisfaction and comfort, and build stronger loyalty toward hospital services